Validation of the Ectasia Risk Score System for Preoperative Laser in Situ Keratomileusis Screening - Randleman, J. Bradley (2008)
PURPOSE: To validate the Ectasia Risk Score System for identifying patients at high risk for developing ectasia after laser in situ keratomileusis (LASIK).. DESIGN: Retrospective case-control study METHODS: Fifty eyes that developed ectasia and 50 control eyes with normal postoperative courses after LASIK were analyzed and compared using the previously described Ectasia Risk Score System, which assigns points in a weighted fashion to the following variables: topographic patter, predicted residual stromal bed thickness (RSB), age, preoperative corneal thickness (CT), and manifest refraction spherical equivalent (MRSE). RESULTS: In this series 92% of eyes with ectasia were correctly classified as being at high risk for the development of ectasia, while 6% of controls were incorrectly classified as being at high risk for ectasia. (p< 1 × 10(−10)). Significantly more eyes were classified as high risk by the ectasia risk score than by traditional screening parameters relying on abnormal topography or residual stromal bed thickness less than 250 μ (92% vs. 50%, p <0.00001). There was no difference in the sensitivity or specificity of the Ectasia Risk Score System in the population from which it was derived and this independent population of ectasia cases and controls. CONCLUSION: The Ectasia Risk Score System is a valid and effective method for detecting eyes at risk for ectasia after LASIK and represents a significant improvement over previously utilized screening strategies.